Tantangan dalam Pembentukan dan Proses Pembelajaran Paduan Suara: analisis - Nicolhas Jurdy Wijaya (Program Studi Pendidikan Musik, 2026)
Choral singing constitutes an essential component of music education that supports the development of musical, social, and affective competencies among students. However, the processes of choir formation and choral learning continue to face various challenges that may hinder the effectiveness of instruction. This study aims to analyze the main challenges encountered in choir formation and choral learning, as well as their pedagogical implications within the context of arts education. Employing a qualitative descriptive approach, this research is based on a conceptual review through literature analysis of national and international journal articles published within the last five years. Data were analyzed thematically by categorizing challenges into pedagogical, vocal-technical, and social-managerial dimensions. The findings reveal that disparities in students’ vocal abilities, limited application of adaptive instructional strategies, ineffective rehearsal management, and low levels of motivation and attendance are dominant challenges. These results highlight the importance of collaborative, student-centered, and process-oriented pedagogical approaches in improving the quality and sustainability of choral learning in educational settings